2008
DOI: 10.1097/brs.0b013e31817e69d3
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs for Low Back Pain

Abstract: The evidence from the 65 trials included in this review suggests that NSAIDs are effective for short-term symptomatic relief in patients with acute and chronic low back pain without sciatica. However, effect sizes are small. Furthermore, there does not seem to be a specific type of NSAID, which is clearly more effective than others. The selective COX-2 inhibitors showed fewer side effects compared with traditional NSAIDs in the randomized controlled trials included in this review. However, recent studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
21

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(140 citation statements)
references
References 61 publications
2
117
0
21
Order By: Relevance
“…Conventional treatments such as nonsteroidal antiinflammatory drugs (NSAIDs) provide effective short-term back pain relief but do not alter the progression of disc degeneration [55,76]. There is conflicting evidence about the effects of NSAIDs on intervertebral disc tissues.…”
Section: Oral Treatmentsmentioning
confidence: 99%
“…Conventional treatments such as nonsteroidal antiinflammatory drugs (NSAIDs) provide effective short-term back pain relief but do not alter the progression of disc degeneration [55,76]. There is conflicting evidence about the effects of NSAIDs on intervertebral disc tissues.…”
Section: Oral Treatmentsmentioning
confidence: 99%
“…A Cochrane review of 65 randomized controlled trials found evidence that NSAIDs are effective for the management of chronic low back pain pain, but effect sizes were indicative of only a small treatment effect (Roelofs et al, 2008). The evidence presented in this Cochrane review suggested that different NSAIDs, including cyclooxygenase-2 inhibitors, show similar efficacy in patients with chronic low back pain.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 82%
“…Evidence from meta-analyses provide evidence that NSAIDs are moderately more effective than acetaminophen (Lee et al, 2004;Roelofs et al, 2008), and chronic low back pain guidelines also state that NSAIDs are more effective (Airaksinen et al, 2006;Chou et al, 2007). In patients with osteoarthritis, effect sizes for NSAIDs are substantially higher than with acetaminophen but nonetheless correspond to a small treatment effect (Zhang et al, 2010).…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Основной механизм действия НПВП заключается в блокировании фер-мента, участвующего в синтезе меди-аторов (посредников) воспаления и боли, а также в расширении сосудов. ЦОГ-2-селективные НПВП имели меньше побочных эффектов, чем неселективные [118]. Селективные ингибиторы ЦОГ-2 (нимесулид, целекоксиб, валдекоксиб, мелоксикам, лорноксикам), обладая противовоспалитель-ной и анальгезирующей активностью, обеспечивают большую безопасность у пациентов с заболеваниями желудочно-кишечного тракта.…”
Section: лечениеunclassified